(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The development of water and sewage networks, and the increasing number of waste-water treatment plants causes a continuous increase in the amount of sewage sludge. One of the forms of disposal and management may be their use of fertilizer. They are able to replace costly chemical fertilizers, especially in the fertilization of plants uncon-trolled consumer goods. Such a plants is willow, which research has shown responds very well to increase yields in the application of sewage sludge. The article describes both the advantages and limitations of the agricultural use of sewage sludge in willow fertilization.